Human permanent teeth are divided into two parts at the cemento-enamel junction in the divine golden ratio - Rahul Anand; Sachin C Sarode; Gargi S Sarode; Shankargouda Patil (Indian Journal of Dental Research, 2017)
Aim: The aim of this study is to find out whether tooth length (crown length + root length) follows the rule of most divine and mysterious phi (ϕ) or the golden ratio. Methods: A total of 140 teeth were included in the study. The crown-root ratio was manually calculated using vernier caliper and its approximation to golden ratio or the divine number phi (ϕ) was examined. Results: The average root-crown ratio (R/C) for maxillary central incisor was 1.627 ± 0.04, and of its antagonist, mandibular central incisor was 1.628 ± 0.02. The tooth-root ratio (T/R) for the same was 1.609 ± 0.016 and 1.61 ± 0.008, respectively. Similar values were appreciated for lateral incisors where the R/C ratio in the maxillary and mandibular teeth was 1.632 ± 0.015 and 1.641 ± 0.012 and the T/R ratio was 1.606 ± 0.005 and 1.605 ± 0.005, respectively. Conclusion: On measuring the tooth length in linear fashion from the cusp tip to the root apex, we found that the tooth was divided into two parts at the cemento-enamel junction in the golden ratio. This information can be exploited in restorative and implant dentistry in future.